2018
DOI: 10.1192/bjp.2017.64
|View full text |Cite
|
Sign up to set email alerts
|

How do doctors deliver a diagnosis of dementia in memory clinics?

Abstract: Doctors are naming dementia to patients. Direct approaches reflect attempts to ensure clear diagnosis. Downplaying and avoiding prognosis demonstrates concerns about preserving hope but may compromise understanding about and planning for the future. Declaration of interest None.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(29 citation statements)
references
References 34 publications
0
29
0
Order By: Relevance
“…23 A study of diagnostic practices in UK memory services also found that doctors tended to focus on positive aspects and downplay the progressive nature and prognosis of dementia. 24 Clinicians distinguished between defining dementia as progressive and terminal. They often had to repeat to family that dementia was progressive, raising the question as to how well the person with dementia and family interpret and understand the information provided.…”
Section: Discussionmentioning
confidence: 99%
“…23 A study of diagnostic practices in UK memory services also found that doctors tended to focus on positive aspects and downplay the progressive nature and prognosis of dementia. 24 Clinicians distinguished between defining dementia as progressive and terminal. They often had to repeat to family that dementia was progressive, raising the question as to how well the person with dementia and family interpret and understand the information provided.…”
Section: Discussionmentioning
confidence: 99%
“…Primarily, whilst this study has information about caregivers' DRs, we do not have information about how the diagnosis was conveyed to the caregivers. This information may have influenced their DRs; for instance, healthcare professionals may use terms such as 'memory problems' during diagnostic meetings or highlight the uncertainty of the diagnosis (Dooley, Bass, & McCabe, 2018). This study used a quantitative approach; had the study incorporated qualitative data collection, this would have allowed further exploration of the caregivers' responses.…”
Section: Discussionmentioning
confidence: 99%
“…A small study conducted in UK memory clinics in 2012 found doctors usually avoided the word 'dementia' (Peel, 2015). However, a more recent video observation of diagnostic feedback meetings 2014-2016 found that dementia was always named (Dooley et al, 2018). However, the doctors described strategic and individualised use of 'dementia' and 'Alzheimer's' labels.…”
Section: Discussionmentioning
confidence: 99%
“…A small observational study of 5 patients during memory clinic consultations in 2015 found that doctors tended not to explicitly name "dementia" or "Alzheimer's Disease" (Peel, 2015). However, a more recent study of UK memory clinics found that doctors consistently named dementia when delivering the diagnosis (Dooley, Bass, & McCabe, 2018). This may potentially reflect an increasing culture of disclosure in recent years (Hellstrom & Torres, 2013).…”
Section: Introductionmentioning
confidence: 99%